(untitled) (Fiep Bulletin - online, 2016)
One of the industry sectors that have been emphasized by poor working conditions and lack of security for workers is the sector of slaughterhouse and meat processing companies. This article aims to conduct an Ergonomic Work Analysis (EWA) by TOR-TOM methodology in various sectors of a small meat processing industry, as well as compare the times found for fatigue recovery determined by the method with breaks of values ??for rest stipulated by NR 36. Therefore, we made several visits to the analyzed sectors and applied a checklist based on the NR 17 and NR 36 in order to verify some of the items that the meat processing would need to adjust according to the Standards requisites. The results proved that the company must urgently adapt Standards (17 and 36) both to provide better working conditions, and to avoid fines and even the closure of the establishment. It was concluded that the activities in sectors considered more critical in the process had large ergonomic problems.